2019
DOI: 10.1016/j.ajpath.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

CD147/Basigin Deficiency Prevents the Development of Podocyte Injury through FAK Signaling

Abstract: Podocytes, which are susceptible to injury by various stimuli and stress, are critical regulators of proteinuric kidney diseases, regardless of the primary disease and pathogenesis. We further confirmed a significant correlation between urinary CD147/basigin (Bsg) levels and proteinuria in patients with focal segmental glomerulosclerosis. However, the molecular mechanism of podocyte injury involving Bsg is not fully understood. Here, the involvement of Bsg in the pathogenesis of podocyte injury was elucidated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…By exacerbating kidney injury, CD147 increases proteinuria, which has an additional exacerbating effect on the progression of renal allograft failure. Similar results were obtained by Yoshika et al, who established a positive correlation between urine CD147 levels and urine protein concentrations [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…By exacerbating kidney injury, CD147 increases proteinuria, which has an additional exacerbating effect on the progression of renal allograft failure. Similar results were obtained by Yoshika et al, who established a positive correlation between urine CD147 levels and urine protein concentrations [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…Yoshioka et al reported that Bsg/CD147 is rarely expressed in healthy podocytes. In adriamycin-induced nephropathy, increases in Bsg expression and proteinuria are mediated by increases in focal adhesion kinase signaling [35]. In their clinical study, Musial et al reported the serum concentrations of CD147 along with other fibrosis markers, such as transforming growth factor beta (TGF-β) levels, in children with CKD [36].…”
Section: Cd147 (Extracellular Matrix Metalloproteinase Inducer/basigi...mentioning
confidence: 99%
“…For in vitro inhibition of MCT1 (siRNA ID, s73853) or BSG (siRNA ID, s63099), RNA interference was performed using gene expression silencing RNA (Thermo Fisher Scientific). Transfection was performed using Lipofectamine RNAiMAX (Life Technologies, Thermo Fisher Scientific) for siRNA according to the manufacturer's protocol as described previously (48).…”
Section: Methodsmentioning
confidence: 99%